Spray freeze granulation of submicron alumina and its sintering behavior via spark plasma sintering - Liu Wei; Xie Zhipeng (Science of Sintering, 2015)
Spray freeze granulation is an improved method based on spray granulation, solving many limitations of spray granulation. In this work, spray freeze granulation of submicron alumina is performed to explore the possibility of industrial-scale production of dense alumina via spark plasma sintering. Powder pretreatment such as sedimentation and the selection of granules with the appropriate size are employed for the maximum use of the high qualified as-prepared granules and granule sliding, which would provide a guidance for the industrial-scale production. Debound granules were densified via SPS and the corresponding sintering behaviors such as the recorded shrinkage and shrinkage rate were discussed. The comparison of sintering behaviors between granulated and as-received powder are conducted to identify the role of spray freeze granulation in sinterability for dense alumina. The Vickers hardness (Hv) and the fracture toughness (KIC) of the freeze granulated body are higher than the corresponding properties of the as-received body due to the more homogenous microstructure with little agglomeration in the particle packing after freeze granulation.